Roles of Prediction as a Parameter of Text Organisation - Meurer, José Luiz (The ESPecialist, 2012)
Frequently in written texts one block of information leads the reader to predict the occurrence of a second block of information in the same text. This phenomenon is known as prediction. In structural terms, prediction in written monologues is similar to the anticipation of information which occurs in adjacency pairs: as the reader/speaker meets a first pair-part, the expectation is set up that a coherent second pair-part will also occur in the text. A systematic predictive-predicted relation is thus established. In this paper, I discuss the organisation and function of two different types of prediction in written monologues. The data analysed are excerpts from the language of self-help counselling, a pervasive type of contemporary mass culture written discourse which has not received much attention in the area of text/discourse analysis. The analysis presented here is relevant for the description of written text structure, for reading pedagogy and applied linguistics.